1994
DOI: 10.1055/s-2006-959568
|View full text |Cite
|
Sign up to set email alerts
|

In VitroSynergism of ConcentratedAllium sativumExtract and Amphotericin B againstCryptococcus neoformans

Abstract: Allium sativum (garlic) derived preparations are used alone or with amphotericin B in Asia to treat human systemic fungal infections and cryptococcal meningitis. To evaluate the scientific merit of using allicin-derived compounds as an anti-fungal drug, we prepared a concentrated A. sativum extract that contained 34% allicin, 44% total thiosulfinates, and 20% vinyldithiins. We found that the concentrated extract possessed potent in vitro fungistatic and fungicidal activity against 3 different isolates of Crypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 3 publications
0
28
0
Order By: Relevance
“…Davis et al (1994) show an in vitro synergistic fungistatic activity effect of concentrated Allium sativum extract with amB against C. neoformans. Another study also showed an increase in antifungal activity of amB in the presence of acteoside, a phenylethanoid glycoside from Colebrookea oppositifolia (Ali et al, 2011).…”
Section: Resultsmentioning
confidence: 79%
“…Davis et al (1994) show an in vitro synergistic fungistatic activity effect of concentrated Allium sativum extract with amB against C. neoformans. Another study also showed an increase in antifungal activity of amB in the presence of acteoside, a phenylethanoid glycoside from Colebrookea oppositifolia (Ali et al, 2011).…”
Section: Resultsmentioning
confidence: 79%
“…Minimum growth inhibitory concentrations (MICs) of AmB, AmBDs and MC12 were determined by the twofold broth dilution method, applying the chequerboard technique (Davis et al, 1994;Tanaka et al, 2000). Cells were grown overnight in YPD medium containing 1 % yeast extract (Difco Laboratories), 2 % bacto-peptone (Difco Laboratories), and 2 % D-glucose, with vigorous shaking at 30 uC.…”
Section: Methodsmentioning
confidence: 99%
“…MICs of PMB and allicin were determined against Escherichia coli IFO 3545, Bacillus subtilis IFO 3007, S. cerevisiae W303-1A, C. albicans IFO 1061, Aspergillus fumigatus IFO 5840, and A. niger ATCC 6275 by 2-fold broth dilution method applying the checkerboard technique [19]. Cells of bacterial strains were grown overnight in 3.0% nutrient broth (Nissui Co., Tokyo, Japan) with vigorous shaking at 30°C, and diluted with the same medium to 10 6 cells/ml.…”
Section: Measurement Of Cell Growth and Viabilitymentioning
confidence: 99%